A Critical Discourse Analysis on Controversial Case of Death Penalty for Mental Disability in Online News - Nabillah, Muchamad Rifqi Nabillah; Triyono, Sulis; Salsabila, Hanania (EDUPEDIA Publisher, 2024)
This research aimed to find out the linguistics aspects that were used by each media in presenting the news about the controversial case of death penalty for man with mental disability and to discover the practice discourse, linguistics aspect produced and social practice that underlie the linguistics aspects used in issuing the discourse. The data of this study was the online news that was published by Detiknews, Okenews, Sindonews.com, Tribunnews, Tempo.com, merdeka.com. The method used in this study was a qualitative research method to approach critical discourse analysis. This study applied the critical discourse analysis theory of Norman Fairclough encompassing text analysis (microstructure), discourse practice (mesostructured) and sociocultural practice (macrostructure). From the result, we found that each media has different linguistics, aspect such as in selecting the dictions or phrases due to each media has each view, ideology and general description. In social view shows that society was disappointed to the Singapore government in doing the despicable and cruel action to the disabled people who need to be protected and does not consider the law of human right .